First Geographical Record of Corymorpha bigelowi (Cnidaria: Hydrozoa, Corymorphidae) in the Northern Red Sea Coast of Egypt, Based on Morphological Description - Fedekar Fadel Madkour; Walaa Safwat Zaghloul; Samya Hussein Mohammad (International Marine Science Journal, 2019)
The Anthomedusae species, Corymorpha bigelowi Maas, 1905 (Cnidaria: Hydrozoa, Corymorphidae), was recorded in the northern Red Sea fauna, representing it
Keywords: Hydromedusae